Rehabilitación mediante metodología AASTHO 93 para mejorar el estado del pavimento flexible del tramo Trujillo Huanchaco, 2023 - Alfaro Rodríguez, Froilán (2023)
The present research was carried out in the city of Trujillo, at the National University of Trujillo, the rehabilitation was proposed using AASTHO 93 methodology to improve the condition of the flexible pavement of the Trujillo Huanchaco section. For the development of the thesis, the criterion of inclusion was used, having chosen the Trujillo Huanchaco section with 9.2 km in length; data collection was carried out with the help of data collection techniques, such as observation and documentary analysis, and the instruments used were observation guides and summary sheets, obtained from the AASHTO Guide and pavement manuals. The general objective was to determine the rehabilitation using AASTHO 93 methodology to improve the condition of the flexible pavement of the Trujillo-Huanchaco section, due to the high traffic and the high traffic flow on this road, as well as the flaws present in some points of the pavement, causing discomfort to users. The results determined in our investigation are detailed as follows: a PCI condition index of 44 indicating a pavement in regular condition, pavement with a serviceability index equal to 2.66522 and a regularity index of 3.47165 indicating a condition of the flexible pavement with a regular condition; also the characteristic deflections of 303. 82 µm in the flexible pavement of the left roadway and 299.50 µm in the flexible pavement of the right roadway; having as a conclusion that the condition of the flexible pavement of the observed roadway has a REGULAR condition, therefore a rehabilitation of the functional reinforcement type (resurfacing) is needed, proposing a 10 cm thick resurfacing.